Pelatihan Penulisan Artikel Ilmiah dan Buku bagi Guru-Guru SD, SMP, dan Madrasah Aliyah di Alazhar Asyarif Sumatera Utara - Gunawan, Gunawan; Siregar, Efrizal; Agustina, Ika; Murtopo, Murtopo; Andrian, Andrian; Anwar, Khairil; Lubis, Reniwati (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
This community service aims to enhance the capacity of teachers at Alazhar Asyarif North Sumatra's elementary, junior high, and Madrasah Aliyah schools in scientific writing and book authoring. The training is designed to equip teachers with the necessary knowledge and skills to produce high-quality scientific papers and to create books that can be used as teaching materials. The methods used in this training include presentations, interactive discussions, and hands-on practice. The results of the training indicate an improvement in teachers' understanding and skills in writing scientific papers and books, as well as a strong motivation to continue developing these competencies.